Оптимізація управління конкурентоспроможністю підприємства в умовах ринкових змін - Онищенко, Христина Анатоліївна; Onyshchenko, Khrystyna (ЦНТУ, 2025)
Кваліфікаційна робота присвячена комплексному аналізу процесів управління конкурентоспроможністю підприємства в умовах змінного ринкового середовища. The qualification paper is devoted to a comprehensive analysis of the processes of managing enterprise competitiveness in a changing market environment.
Optimization of the management of the competitiveness of the enterprise in the conditions of market changes
Keywords: конкурентоспроможність; управління; стратегія; competitiveness; management; strategy